2014
DOI: 10.1007/s11357-014-9628-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dietary exposure to low concentration of dichloroacetic acid promoted longevity and attenuated cellular and functional declines in aged Drosophila melanogaster

Abstract: Dichloroacetic acid (DCA), a water disinfection by-product, has attained emphasis due to its prospect for clinical use against different diseases including cancer along with negative impact on organisms. However, these reports are based on the toxicological as well clinical data using comparatively higher concentrations of DCA without much of environmental relevance. Here, we evaluate cellular as well as organismal effects of DCA at environmentally and mild clinically relevant concentrations (0.02-20.0 μg/ml) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…7 It is employed in chemical screening and toxicology studies whereby behaviours, such as oviposition, 8 movement, 9 foraging, 10 avoidance, 11 and mating, 12 are assayed in response to environmental toxicants. 1,[12][13][14] Oviposition is the process of egg-laying in D. melanogaster that is dependent on responses of the fly to environmental stimuli (such as chemicals, physical conditions of the substrate, temperature, light, population density, and humidity). [15][16][17][18][19] D. melanogaster possesses sensory neurons (such as taste 20,21 and touch 22,23 sensing systems) to detect various environmental cues prior to selecting preferred sites for oviposition and egg laying.…”
mentioning
confidence: 99%
“…7 It is employed in chemical screening and toxicology studies whereby behaviours, such as oviposition, 8 movement, 9 foraging, 10 avoidance, 11 and mating, 12 are assayed in response to environmental toxicants. 1,[12][13][14] Oviposition is the process of egg-laying in D. melanogaster that is dependent on responses of the fly to environmental stimuli (such as chemicals, physical conditions of the substrate, temperature, light, population density, and humidity). [15][16][17][18][19] D. melanogaster possesses sensory neurons (such as taste 20,21 and touch 22,23 sensing systems) to detect various environmental cues prior to selecting preferred sites for oviposition and egg laying.…”
mentioning
confidence: 99%
“…ROS level was detected through DCF fluorescence [ 23 ]. The supernatant (5 μl) was loaded with 295 μl of DCFH2-DA with a final concentration of 10 μM and then incubated at 37°C for 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…A previous publication similarly utilized DCA to activate voltage-gated K þ channels in Drosophila (Dawson-Scully et al, 2010); however, this study did not directly demonstrate DCA activation of voltage-gated K þ channels in neurons or muscles. Recently, it has been shown that mature flies fed DCA display acute increases in ROS production and oxidative stress (Pandey et al, 2014). Therefore, the DCA-induced decrease in time to synaptic failure in Slo 4 mutants could potentially be attributed to DCA activating K þ channels, exacerbating oxidative stress, or modulating other metabolic processes.…”
Section: Potential Downstream Targets Of the Pkg Pathwaymentioning
confidence: 99%